O comportamento do consumidor no desperdício de alimentos em domicílios brasileiros - Deliberador, Lucas Rodrigues (2023)
Food waste represents one third of all food produced globally. While this problem is characteristic of developed countries, Brazil is among the nations that waste the most food, which adds to the challenge of feeding 52 million people who still live in a situation of food insecurity in the country. In order to contribute towards mitigating the problem, this study identified how aspects of consumer behavior influence food waste in Brazilian households. Through a Systematic Literature Review (SLR), it was identified the drivers that may lead consumers to waste food in their homes. An analytical framework based on an extension of the Theory of Planned Behavior (TPB) was proposed to empirically measure these determinants of food waste. For this analysis, the study conducted a survey of 2047 Brazilian consumers. Structural Equation Modeling was used as a data analysis technique. The results confirmed eleven of the seventeen proposed hypotheses. Environmental concerns, economic concerns, feelings of guilt, subjective norms, and perceived behavior control had significant causality on consumers' intention to reduce food waste. On the other hand, perceived behavioral control, intention, home planning, convenience food consumption, suboptimal food consumption, and good provider identity had significant causality on food wasting behavior. With the results of the study, it is expected, in addition to understanding the behavior of Brazilian consumers regarding food waste in households, to contribute to waste prevention policies and develop future research agendas in this area. In addition to these contributions, the study may contribute to the scarce literature on this theme in emerging countries.